ANALYSIS OF CHANGES IN NATURAL AND MAN-MADE CONDITIONS, ECOLOGICAL AND HYDROGEOLOGICAL STATE OF MINES (American Journal of Pedagogical and Educational Research, 2024)
V state: Izmenenie soderjaniya rudnika i okrujayushchey ego rastitelnosti svyazano s izmeneniem klimata i perspektivami vodnykh resursov. Data obtained from system monitoring, dayut information and processes, management of ecological and hydrogeological conditions, ix prichinax and merah, prinimaemyx protiv etix processesov. It is necessary to develop an effective and protective strategy for the protection of the ecological environment, the preservation of water resources and the minimization of the impact of anthropogenic conditions on the environment.